Causes of Congenital Malformations. Issue 2 (29th January 2018) - Toufaily, M. Hassan; Westgate, Marie‐Noel; Lin, Angela E.; Holmes, Lewis B.
Abstract : Background: Many different causes of malformations have been established. The surveillance of a consecutive population of births, including stillbirths and elective terminations of pregnancy because of fetal anomalies, can identify each infant with malformations and determine the frequency of the apparent etiologies. This report is a sequel to the first such analysis in the first 10 years of this Active Malformations Surveillance Program (Nelson and Holmes, 1989 ). Methods: The presence of malformations was determined among 289, 365 births over 41 years (1972–2012) at the Brigham and Women's Hospital in Boston. The abnormalities were identified from the review of the examination findings of the pediatricians and consultants and diagnostic testing for the live‐born infants and the autopsies of the fetuses in elective terminations and stillbirths. Results: A total of 7020 (2.4%) infants and fetuses with one or more malformations were identified with these apparent etiologies in 26.6%: Mendelian disorders, including infants with postaxial polydactyly, type B; chromosome abnormalities; vascular disruption; complications of monozygous twinning; and environmental factors. The malformations of unknown etiology were a much larger group. Conclusion: While several causes of malformations have been identified, many remain unexplained. Combining the ascertainment in a future surveillance programs with genome sequencing and chromosome microarray analysis will increase significantly the number of malformations attributed to genetic mechanisms. Birth Defects Research 110:87–91, 2018.© 2018 Wiley Periodicals, Inc.